2023
DOI: 10.1038/s41598-023-33806-8
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota induces hepatic steatosis by modulating the T cells balance in high fructose diet mice

Abstract: Metabolic diseases are often associated with high fructose (HF) consumption. HF has also been found to alter the gut microbiota, which then favors the development of nonalcoholic fatty liver disease. However, the mechanisms underlying of the gut microbiota on this metabolic disturbance are yet to be determined. Thus, in this study, we further explored the effect the gut microbiota concerning the T cells balance in an HF diet mouse model. We fed mice 60% fructose-enriched diet for 12 weeks. At 4 weeks, HF diet … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…ATB decreased intestinal A. muciniphila abundance in mice. Besides, ATB increased the content of IL‐6, a proinflammatory cytokine, 25 by 1.75‐fold and that of LBP, a marker of intestinal microbial leakage, 26 by 1.60‐fold, in the serum of mice. LPS, bound with LBP, is detected in the blood when the intestinal barrier is damaged 27 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…ATB decreased intestinal A. muciniphila abundance in mice. Besides, ATB increased the content of IL‐6, a proinflammatory cytokine, 25 by 1.75‐fold and that of LBP, a marker of intestinal microbial leakage, 26 by 1.60‐fold, in the serum of mice. LPS, bound with LBP, is detected in the blood when the intestinal barrier is damaged 27 .…”
Section: Resultsmentioning
confidence: 96%
“…ATB decreased intestinal A. muciniphila abundance in mice. Besides, ATB increased the content of IL-6, a proinflammatory cytokine, 25 by 1.75-fold and that of LBP, a marker of intestinal microbial leakage, 26 The plating chart and counting histogram following A. muciniphila intervention in a medium containing wolfberry (L: 0.012 g/mL, M: 0.018 g/mL and H: 0.024 g/mL), yam (L: 0.03 g/mL, M: 0.045 g/mL and H: 0.06 g/ mL) or chrysanthemum (L: 0.01 g/mL, M: 0.015 g/mL, and H: 0.02 g/mL). (C) The orthogonal method was applied to explore the optimal concentration ratio of WYC to enhance A. muciniphila proliferation.…”
Section: A Muciniphila Promoted the Abundance Of A Muciniphila In Atb...mentioning
confidence: 94%
“…While the exact mechanisms are still being elucidated, key lipogenic regulator genes such as chREBP and SREBP1 are shown to be increased with fructose 45,46 ; future investigations into the effects of mannose on these targets and on lipidomic profiling would be of interest. Lastly, it has been shown that fructose can cause direct intestinal epithelial damage 47 and microbiome dysbiosis 48 , both of which result in gut inflammation via increased permeability, microbial/LPS translocation, and T cell modulation. These changes ultimately contribute to pathogenesis of MASLD.…”
Section: Discussionmentioning
confidence: 99%
“… Disease stages Role of Tregs Factors regulating Tregs Mouse/Human Treg quantity Type of Treg study Potential targets/Clinical insights Year/Ref. Cells interacting Liver Periphery Steatosis Preventing immune-mediated liver injury Anti-effector T cells H ↓ (Blood) In vivo 2016 29 Hepatocytes Neutrophils γδT cells Th1 cells Th17 cells Anti-Th17 cells Ferroptosis M (SAM) In vivo Porphyromonas gingivalis 2023 46 Anti-Th1 cells Gut microbiota M (HFD) ↓(MLN) In vivo Fecal microbiota transplantation 2023 47 Anti-effector T cells Gut microbiota M (HFD) ↓ (MLN) In vivo Administration of Lactobacillus 2019 48 Preventing inflammation Oxidative stress M (HFD) → (Spleen) In vivo & vitro Antioxidant 2007 33 Preventing insulin resistance Improving insulin tolerance Adiponectin M (HFD) In vivo Adiponectin-expressing Treg precursors 2021 49 Anti-insulin resistance ...…”
Section: Treg: a Double-edged Sword In Masldmentioning
confidence: 99%
“…The unique visceral adipose tissue-resident Tregs are regulated by peroxisome proliferator-activated receptor (PPAR)-γ, 42 and can be upregulated by treating PPAR-γ agonist to attenuate MASLD in an HFD mouse model. 50 The suppressive function of Tregs on effector T cells plays a critical role in MASH, 47 , 48 , 52 , 54 , 55 and the equilibrium between Tregs and Th17 cells has long been regarded as an indicator to assess the degree of inflammation in the MASH liver. 46 , 53 Evidence has substantiated the role of Tregs in mitigating insulin resistance in mice and patients with MASLD, 49 , 50 , 51 , 57 thereby constraining the subsequent metabolic inflammation.…”
Section: Treg: a Double-edged Sword In Masldmentioning
confidence: 99%